A close-up study to EFL Learners 'Examination Anxiety –the case of second year University of M`sila - Mebrouk Nour Elhouda, Abdelaziz Soumia (My University, 2021)
Anxiety is considered one of the principal factors that affect learners’ cognitive potentials to achieve high levels of outcomes. Its symptoms start with the learners’ preparation, sitting for tests and even after. Its various types can cause serious disorders at the level of the body, the mind and the emotions. It is a psychological trait that curbs learning and baffles teachers in their continuous evaluation even to smart students. In this work, the aim is to shed lights on this psychological phenomenon that creates fear and fright and forces learners even to relinquish in their educational pursuit of knowledge. To unveil the truth about the intricacies of this case, a close- up investigation to this problem was used. A descriptive, analytical and triangulation mixed methods were used in the collection of data through surveys. Two questionnaires were distributed to students and teachers with the intent to collect data in terms of statistics, scales and open-ended questions. The analysis to the questionnaires amply revealed the serious negative effects anxiety can cause to learners’ achievement. Teachers can help solve this problem by briefing learners all the year through and promote intelligible measurements to reduce anxiety to its minimum levels.